Governance Of State University Joint Entrance Selection (SBMPTN) During COVID 19 Pandemic - Imanudin Kudus; Heru Nurasa; Ida Widianingsih; Nina Karlina (Aliansi, 2022)
The 2020 State Higher Education Entrance Joint Selection (SBMPTN) is carried out completely computer-based (CBT), with the number of participants served as many as 713,319 participants which in its implementation requires the availability of an adequate number of test equipment at each State University Computer-Based Test (CBT) Center. This has an impact on the length of the exam administration time with a large number of exam sessions. This condition requires good governance related to the assignment of people in the administration of the State University (CBT) Center especially in the conditions of the Covid 19 pandemic, where the implementation of the CBT SBMPTN in 2020 is faced with conditions of crowd restrictions and the application of health protocols that are strictly enforced. Of course, it requires unusual treatment.This study aims to see how the governance of the exam implementation in the Covid-19 pandemic conditions, covering institutional aspects, human resources, exam systems and infrastructure from planning, implementation to evaluation. Practically, this study aims to provide input for policy improvement in the form of recommendations for good governance models in the implementation of the Joint Selection for State Universities in Indonesia during the Covid 19 pandemic.The research was conducted using qualitative methods. The results of this study indicate that the implementation of computer-based examination governance in the Covid-19 pandemic requires a breakthrough outside the normal conditions of the examination, especially in the substance and number of items tested as well as the allocation of participants in the session and exam room.